Arp2/3 and Unc45 maintain heterochromatin stability in Drosophila polytene chromosomes. - Dialynas, G.; Delabaere, L.; Chiolo, I. (Experimental biology and medicine (Maywood, N.J.), 2019)
Repairing DNA double-strand breaks is particularly challenging in pericentromeric heterochromatin, where the abundance of repeated sequences exacerbates the risk of ectopic recombination. In Drosophila Kc cells, accurate homologous recombination repair of heterochromatic double-strand breaks relies on the relocalization of repair sites to the nuclear periphery before Rad51 recruitment and strand invasion. This movement is driven by Arp2/3-dependent nuclear actin filaments and myosins ability to walk along them. Conserved mechanisms enable the relocalization of heterochromatic repair sites in mouse cells, and defects in these pathways lead to massive ectopic recombination in heterochromatin and chromosome rearrangements. In Drosophila polytene chromosomes, extensive DNA movement is blocked by a stiff structure of chromosome bundles. Repair pathways in this context are poorly characterized, and whether heterochromatic double-strand breaks relocalize in these cells is unknown. Here, we show that damage in heterochromatin results in relaxation of the heterochromatic chromocenter, consistent with a dynamic response. Arp2/3, the Arp2/3 activator Scar, and the myosin activator Unc45, are required for heterochromatin stability in polytene cells, suggesting that relocalization enables heterochromatin repair also in this tissue. Together, these studies reveal critical roles for actin polymerization and myosin motors in heterochromatin repair and genome stability across different organisms and tissue types.